Study on preparation and properties of water swellable rubber modified by interpenetrating polymer networks - Jiang X L et al. (Plastics,Rubber and Composites, 2013)
A novel water swellable rubber(WSR) has been prepared by blending nitrile rubber(NBR),carbon black and other additives with cross-linked sodium polyacrylate(CSP),which was modified by interpenetrating polymer network technology with cross-linked P(AA-co-BA).The structure of WSR was characterised by SEM.The mechanical properties,water swelling ratio by mass and the percentage loss of CSP in the WSR were invetigated.The results showed that the modified CSP grains can be dispersed well in the NBR and that it resulted in increase of mechanical properties and water swelling ratio and in decrease of percentage loss of CSP compared with the unmodified one.When the percentage content of cross-linked P(AA-co-BA) used to modify CSP reached 30;, the tensile strength, elongation at break and water swelling ratio of WSR exhibited a maximum value,and percentage loss of CSP exhibited a minimum value.When the content of CSP in WSR was 30 phr, the tensile strength, elongation at break, water swelling ratio and percentage loss of CSP of the WSR containing CSP modified were 11.3 MPa,1943;,532;and 5.8;respectively.
Keywords: Compatibilisation; Cross-linked sodium polyacrylate; Nitrile rubber; Water swellable rubber